Britain's Withdrawal From East of Suez - Pickering, J. author. aut Link
XI, 230 p.
Keywords: After 1945, Britain maintained a great chain of overseas military outposts stretching from the Suez Canal to Singapore. Commonly termed the `east of Suez' role, this chain had long been thought to be crucial for the country's security and its vitality. Nonetheless, British leaders eventually decided to abandon this network of bases. This study provides the most comprehensive explanation of this pivotal decision to date, while also offering insight into the processes of foreign policy change and the decline of great powers.